2010
DOI: 10.1111/j.1095-8312.2010.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Size variation facilitates population divergence but does not explain it all: an example study from a widespread African monkey

Abstract: Subspecific variation is widespread in vertebrates. Within Africa, several mammals have extensive geographic distributions with attendant morphological, ecological, and behavioural variations, which are often used to demarcate subspecies. In the present study, we use a primate species, the vervet monkey, Cercopithecus aethiops, as a case study for intraspecific divergence in widespread mammals, assessed through hard tissue morphology. We examine intraspecific differences in size, shape, and non-allometric shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 63 publications
0
28
1
Order By: Relevance
“…, ; Elton et al. ). Geographic variation in guenon postcrania has received relatively little attention, primarily because of the paucity of specimens available that sample a representative proportion of the total range.…”
Section: Arboreality Terrestriality and Generality In The Guenonsmentioning
confidence: 99%
“…, ; Elton et al. ). Geographic variation in guenon postcrania has received relatively little attention, primarily because of the paucity of specimens available that sample a representative proportion of the total range.…”
Section: Arboreality Terrestriality and Generality In The Guenonsmentioning
confidence: 99%
“…Discriminant function analysis (DFA) was used to assess the degree of similarity of subspecies (Elton et al 2010). The ratio of misclassified and correctly classified individuals, after cross-validation, gives a measure of similarity (Cardini & Elton, 2011).…”
Section: Subspecific Differencesmentioning
confidence: 99%
“…Although geography and spatially-structured environmental variables – such as rainfall and seasonality – explained some of this localized variation, 60–80% remained unexplained. Further study by this group found localized variation within vervets to be of particular interest because of evident plasticity of vervets leading to rapid expansion into previous underutilized areas that could lead to localized adaptive response to microclimates; the authors characterized such local variation as ‘incipient stages in a process of evolutionary radiation’ (Elton et al 2010). Large-scale genetic studies have also attempted to explain taxon-wide variation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite work having been done in this region for quite some time (e.g., Henzi & Lucas, 1980), and the ongoing deep phenotyping being conducted within the area, very little is yet known about local population processes. Although recent extensive taxonomic sampling has been able to compare East African to South African extensions of the pygerythrus range (Haus et al, 2013, Elton et al, 2010) they did not sample sufficiently in South Africa to address local population divergences with any resolution. Such finer scale work has been done in the East African aethiops morph, or grivets, in which evidence was found of mtDNA substructuring despite widespread monotypy in phenotype, perhaps as the result of demographic shifts due to climatic change (Shimada, 2000; Shimada et al 2002).…”
Section: Introductionmentioning
confidence: 99%